Characterizing fatigue associated with sunitinib and its impact on health‐related quality of life in patients with metastatic renal cell carcinoma. Issue 12 (13th March 2014) - Cella, David; Davis, Mellar P.; Négrier, Sylvie; Figlin, Robert A.; Michaelson, M. Dror; Bushmakin, Andrew G.; Cappelleri, Joseph C.; Sandin, Rickard; Korytowsky, Beata; Charbonneau, Claudie; Matczak, Ewa; Motzer, Robert J.
<x xml:space="preserve">Abstract</x> BACKGROUND Using phase 3 trial data for sunitinib versus interferon (IFN)‐α in treatment‐naive patients with metastatic renal cell carcinoma, retrospective analyses characterized sunitinib‐associated fatigue and its impact on patient‐reported health‐related quality of life (HRQoL). METHODS Patients received sunitinib at a dose of 50 mg/day on a schedule of 4 weeks on/2 weeks off (375 patients) or IFN‐α at a dose of 9 MU subcutaneously 3 times per week (360 patients). HRQoL was self‐assessed using the Functional Assessment of Cancer Therapy‐Kidney Symptom Index–15‐item (FKSI‐15) questionnaire, with fatigue assessed using its Disease‐Related Symptoms subscale. Fatigue was also assessed by providers using Common Terminology Criteria for Adverse Events (CTCAE). A repeated‐measures model (M1) and random intercept‐slope model (M2) characterized sunitinib‐associated fatigue over time. Another repeated‐measures model examined the relationship between HRQoL scores and CTCAE fatigue grade. RESULTS M1 demonstrated that the initial increase in patient‐reported fatigue with sunitinib was worst during cycle 1, with mean values numerically better at subsequent cycles; most pairwise comparisons of consecutive CTCAE fatigue cycle means were not found to be statistically significant. M2 demonstrated that the overall trend (slope) for patient‐reported and CTCAE fatigue with sunitinib was not statistically different from 0. The relationship between most HRQoL scores and CTCAE fatigue was close to linear regardless of treatment, with lower scores (worse HRQoL) corresponding to higher fatigue grade. The majority of HRQoL scores were better with sunitinib versus IFN‐α for the same CTCAE fatigue grade. CONCLUSIONS Patients reported worse fatigue during the first sunitinib cycle. However, in subsequent consecutive cycles, less fatigue was reported with no statistically significant worsening. CTCAE fatigue assessment may not fully capture patient treatment experience. Cancer 2014;120:1871–1880. © 2014 American Cancer Society.